Historical trends and future implications of disasters in Honduras - Quesada Román, Adolfo (2024)
In Honduras, a country located in Central America, the prevalence of hydrometeorological disasters due to its geographical location poses a challenge in the context of climate change. However, the lack of local disaster data highlights the need to investigate the primary natural hazards impacting Honduran municipalities. In this regard, the disaster database DesInventar was utilized, covering the period between 1978 and 2015, to identify the most recurrent disasters in terms of frequency and severity. The findings indicate that the municipalities most affected by disasters are mainly located in regions with higher population density, particularly in the municipalities of Distrito Central, San Pedro Sula, Danlí, El Progreso, La Ceiba, and Puerto Cortés. The most common hazards in Honduras are floods, wildfires, landslides, droughts, and storms. The results of this analysis hold crucial value for decision-makers in disaster risk, territorial, and environmental management in Honduras. These data provide a solid foundation for designing effective policies and measures aimed at reducing the adverse impacts of disasters in the country. Moreover, this methodological approach can be applied in developing nations with similar characteristics in other tropical regions, thereby contributing to a more efficient management of risks associated with disasters.